The Spirituality of Music in The Light of al-Sarrāj and al-Hujwīrī - Luthfi Rahman (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2017)
This paper discusses spiritual and fiqh (Islamic Jurisprudence) aspects of music in relation to two classical Sufi masters i.e, Abū Naṣr al-Sarrāj al-Ṭūsi (378/988) and Alī b. Uthmān al-Jullabi al-Ḥujwīrī (465/1072). It particularly focuses on their two masterpieces i.e., Kitāb al-Luma’ and Kashfu al-Maḥjūb. It further compares three specific points; permissibility of music, listening to Quran and poetry and the state of ecstasy in auditing music. Based on this study, it is found that the Sufi Masters observed the matter of spirituality can be combined and approached with strict obedience through rigidly practicing fiqh. Yet, it should be noted that spirituality of music will be of course beyond dicta of jurisprudence by the fact that spirituality is inward thing while shari’ah (which is narrowly used to point religious law) is outward one. As to the matter of listening to Quran and poetry, both sufi masters offer more emphasis on listening Qur’an than poetry or odes. Nevertheless, they did not negate the importance of listening to poetry, poems and odes. It is evidenced by a ḥadīth stating that indeed there is wisdom in every poetry. In terms of the state of ecstasy, the two masters offer tawājud (artificial wajd). Tawājud is aimed to gain wajd by representing to one’s mind the bounties and evidences of God, and thinking of union (ittiḥād) and wishing for the practices of Muslim saints.